Utilizing blogs to foster reflective Practice in student teachers of English Education: A case study from Honduras (Educational Knowledge, 2023)
Reflective practice has become paramount in teacher training programs worldwide. This study examines the use of blogs to document reflective experiences of 28 student teachers during a ten-week period in 2018. The research aims to identify themes related to professional development, level of engagement with reflection, and perceptions of the advantages and disadvantages of utilizing blogs. Employing a constructivist epistemological framework and deductive content analysis, the study derives insights from blog entries and semi-structured interviews. Findings encompass professional development themes such as professional identity, self-efficacy, self-assessment, and self-regulation. While blogs facilitate collaborative learning and experience-sharing, challenges include privacy concerns, time constraints, effort, and variable engagement. Recommendations for pedagogical practice and future research are presented.
Keywords: Blogs; reflective practice; professional development; student teachers; teacher training